Pengembangan Aplikasi Berbasis Web Menggunakan Metode Gamifikasi untuk Materi Bangun Datar pada Sekolah Dasar - Jinan Prabowoningtyas; Sri Mulyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The role of mathematics as a parent of knowledge, tools, guiding thought patterns and forming attitudes, therefore the learning process of Mathematics must be done well. In the classroom learning process, teachers have difficulty delivering material and making students focus, especially in mathematics lessons that require high concentration power. To help the learning process, a web-based learning application model was designed and developed with the integration of gamification mechanisms for elementary school students. The use of analysis methods, prototypes and data collection shows that the system that has been created can be implemented in web-based applications. Then in the test, teachers and students can run the application well and find it helpful in the process of learning mathematics flat wake material.